Anisotropic elastic-plastic deformation of paper: In-plane model. (1st December 2016) - Li, Yujun; Stapleton, Scott Edward; Reese, Stefanie; Simon, Jaan-Willem
Abstract: Laminated paperboard and paper is widely used in packaging products. It generally exhibits highly anisotropic and nonlinear mechanical behavior. The aim of this study is to describe the in-plane material behavior with an orthotropic elastic-plastic model based on the observed experimental behavior. A structural tensor-based approach was applied to model the elastic deformation, while a multi-surface based yield criterion was adopted to describe the yield behavior. The model incorporated nonlinear kinematic and isotropic hardening to capture the anisotropic hardening effect. In the experiment, the compressive yield stress was found to be insensitive to the previous tensile deformation. The proposed model could capture this compression yield stress preserving effect under reverse loading, which in turn reduced the required material parameters as expected. With the material parameters calibrated from a set of simple uniaxial tests in various directions, the model was shown to predict the stress-strain behavior for other orientations satisfactorily. The model was further validated with experiments under complex loading conditions and found to capture the highly anisotropic, elastic-plastic behavior accurately.